Problematika Pengintegrasian Nilai-Nilai Islam Dalam Pembelajaran Ilmu Pengetahuan Alam (IPA) Di Tingkat Sekolah Dasar - Mukminah Mukminah; Hadi Wijaya (Jurnal Ilmiah Mandala Education (JIME), 2015)
Natural sciences (IPA) in common in minister of national education regulation no. 22 years 2006 about content default for elementary education includes in scholarship subject group. Its range zoom for SD /MI is meant to know, behave, and appreciates general science as natural sciences at elementary school (SD). Constitution mandate implies to need it religion point integrations in learning, notably deep general science. So that moslem can get role in solves problem people and also nation faces science or one developing get bearing with IPA. Therefore hereby, be provided that momentous Islamic points deep each science learning processes at schooled can form devout student and gets godfearing. This in writing, study about problem for Islamic point integrations in IPA'S learning one in point of fact is still can't yet give impact that matter.  In this way expected Islamic study (PAI)  not merely as to transfer religious of science one eye, but also islamic's point instilling that its following can be applied by student  in societal life as a moslem